Modification of synthetic polyisoprene by combination with high-density polyethylene - Chernyshov, Sergey V.; Lyusova, Lyudmila R.; Zharylganova, Manizha B.; Nebratenko, Dmitry Y. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The development of elastomeric materials based on synthetic polyisoprene (IR) with high green strength is a rather urgent task, because it allows to replace, completely or partially, the main ingredient - natural rubber in responsible rubber products. The aim of the work was an additional increase in the green strength values of IR and rubber mixtures based on it by its modification with high-density polyethylene of PND 277-73. Methods: The main methods of the research of the technological, physical-mechanical and operational properties were used. All tests conformed to ASTM or ISO standards. Rubber compounds were made in the Haake PolyLab rubber mixer. In parallel with the effects of modification, the influence of the mixing temperature on the main properties of IR and NR based elastomeric materials was investigated. Results: It is shown that the increase in the mixing temperature of NR and IR for 20ºC leads to significant changes in the technological properties of rubber compounds (primarily green strength), as well as the physical-mechanical and operational properties of cured rubber. It has been established that a significant increase in the green strength of the rubber compound is achieved by combining IR with 7 mass. % HDPE. Conclusion: The developed polymer composition based on IR and HDPE has a level of green strength of the rubber compound 2 times higher than that of natural rubber, while maintaining the physical-mechanical and operational characteristics of cured rubbers at the level of natural rubber.The polymer composition IR/HDPE 93/7 can be recommended for use in the manufacture of products whose manufacturing technology requires increased green strength of rubber compounds, including large-sized and all-metal tires.